Mental Accounting of Public Funds - The Flypaper Effect in the Lab - Daniel Hopp; Johannes Becker; Michael Kriebel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We report evidence from a series of laboratory experiments that focus on mental accounting of 'public funds'. Groups of three players decide upon how much to redistribute within the group. We measure the preference to redistribute when transfers are made either out of individual accounts (the players' own money) or out of a common account (the group's money). Since the common account is dissolved after each round and paid out to individuals, its size should not affect the decision to redistribute. The experiment is designed to rule out an anchoring effect. We find that the (relative) size of the common account significantly affects redistribution behavior. Specifically, the transfer increases in the relative size of the common account – but only when the transfer is paid out of the common account (and not out of the individual account). We interpret these findings as evidence for a flypaper effect due to mental accounting and discuss implications for tax policy and government spending.
Keywords: C92; D72; H31; 330; mental accounting; flypaper effect; lab experiments